Evaluating the impact of automation on labour markets in England and Wales - Prashar, A (2018)
Robots are now able to complete many tasks with greater efficiency than humans. This is leading employers to demand different skills from their workforces. Simultaneously, there has been a notable decline in manufacturing employment in the UK. Using data at a local authority level, this thesis shows that industrial robot technology in the transportation manufacturing industry, an empirical proxy for automation, had a negative and statistically significant effect on employment across England and Wales between 1991 and 2001; a period of increasing industrial robot usage in the UK. Using structural parameter estimates for the UK economy, the empirical results suggest that one industrial robot in the transportation manufacturing industry reduced employment by 4.2 workers between 1991 and 2001. This is equivalent to approximately 21,000 job losses over the decade. Upon establishing the result for automation, the empirical analysis is extended to disentangle the impact of automation from trade. It is found that Chinese import exposure had a larger effect than automation between 1991-2001, accounting for approximately 27% of the decline in UK manufacturing employment over the period.